Edukasi Praktik Ecobrick Sebagai Sumber Belajar Anak Usia Dini di Desa Maitara Kota Tidore Kepulauan - Farida Samad; Rita Samad; Zulkifli Zam Zam (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2021)
The purpose of this community service is to provide knowledge about managing plastic waste through Reduce, Reuse, and Recycle (3R). Ecobrick is one of the recycling efforts to minimize the amount of plastic waste movements, by providing knowledge and skills to PAUD Sukun teachers, South Maitara Village, Tidore Islands City in utilizing plastic waste as an educational learning medium. Respondents in this training as many as 20 people, using the lecture method, question and answer, demonstration and discussion. The results of the activity showed that the APE Ecobrick training had a significant impact on the participants, namely knowledge (knowledge) increased by 42.86%, skills increased by 44.26% and ability (ability) became 44.29%. This training is expected to help teachers to create creative and innovative APE using an environmental approach, as well as introduce students to the dangers of plastic waste to the environment, and shape their behavior to recognize and love the environment.